« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques